2014
DOI: 10.1007/s10877-014-9571-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neurophysiological monitoring during spine surgery with total intravenous anesthesia or balanced anesthesia with 3 % desflurane

Abstract: Total intravenous anesthesia (TIVA) with propofol and opioids is frequently utilized for spinal surgery when somatosensory evoked potentials (SSEPs) and transcranial motor evoked potentials (tcMEPs) are monitored. Many anesthesiologists would prefer to utilize low dose halogenated anesthetics (e.g. 1/2 MAC). We examined our recent experience using 3% desflurane or TIVA during spine surgery to determine the impact on propofol usage and on the evoked potential responses. After institutional review board approval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…An additional limitation of our study refers to a potential bias against volatile agents. Some authors recommend 0.5 MAC in combination with narcotics and propofol infusion to facilitate MEP monitoring . In our study BIS guidance led to higher MAC values (i.e.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…An additional limitation of our study refers to a potential bias against volatile agents. Some authors recommend 0.5 MAC in combination with narcotics and propofol infusion to facilitate MEP monitoring . In our study BIS guidance led to higher MAC values (i.e.…”
Section: Discussionsupporting
confidence: 49%
“…As evoked potentials such as SSEPs and MEPs are affected by inhalational agents, this may also count for monitoring of the IAS. In connection with these procedures, depressing effects were not linear, but had a sharp effect above concentrations of 0.5 MAC . However, our endeavours targeted at autonomic nerves and smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
“…tcMEPs were followed-up in a retrospective study of Sloan et al and they formed two groups of cases, as the TIVA (propofol-opioid) and desflurane (3%) (with 50% air) groups; additionally, opioid or propofol was administered in these groups. 10 When the groups were compared regarding the tcMEP and SSEP responses, no statistically significant differences were detected. The retrospective nature of the study, and non-randomized sampling of the patients may be considered as limitations to this study.…”
Section: Resultsmentioning
confidence: 89%
“…tcMEP monitorization, applied for decreasing intraoperative and post-operative neurological deficits in the course of high-risk and long-lasting scoliosis surgery, requires an appropriately developed method of anaesthesia, to achieve good consequences. 10 tcMEP responses are affected and inhibited by anaesthetic agents like neuromuscular blockers, inhalation anaesthetics, and nitrous oxide; however, these responses are known not to be affected by the TIVA method. 11,12 When inhalation anaesthetics were investigated, studies demonstrated that sevoflurane and isoflurane in particular depress the amplitudes of tcMEPs in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, data regarding the relation between galantamine and motor evoked potential is scarce, but a previous clinical study demonstrated that motor evoked potential monitoring is reliable if T2/Tcontrol twitch height is > 0.5 or train of four count is > 2 [10]. Although it has also been reported that balanced desflurane anesthesia and total intravenous anesthesia provided similar hemodynamic responses and recovery profiles [11,12], total intravenous anesthesia is considered to have favorable pharmacokinetic and neurophysiological properties, to enhance the quality of intraoperative motor evoked potentials, and reduce the risk of procedure-related morbidity [13]. After considering the effects of inhalation agents on motor evoked potentials and train of four monitoring, we selected target controlled propofol and remifentanil infusion.…”
Section: Case Reportmentioning
confidence: 99%